2011
DOI: 10.1177/1049732311411927
|View full text |Cite
|
Sign up to set email alerts
|

The Nurse’s Medication Day

Abstract: The medication administration stage of the medication-use process is especially vulnerable to error because errors are least likely to be caught before reaching the patient. Medication administration, however, remains poorly understood. In this article we describe medication administration as observed in an ethnographic study conducted on one medical and one surgical unit. A central finding was that medication administration entailed a complex mixture of varied and often competing demands that temporally struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 39 publications
4
87
1
6
Order By: Relevance
“…The administration of medication requires a complex mixture of varied and often competing responsibilities that structure the nurses’ work day (Jennings et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of medication requires a complex mixture of varied and often competing responsibilities that structure the nurses’ work day (Jennings et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Estudo observacional mostrou resultado semelhante, com média de 9,7 medicamentos prescritos por paciente e variação de 0 a 20 fármacos (19) . Entretanto, os achados de outras pesquisas divergem dos números encontrados, demonstrando uma ampla variação de número de doses prescritas por paciente em diferentes contextos (11,20) . Essas variações em achados de estudos locais e internacionais quanto ao número de medicamentos prescritos por paciente, apontam a necessidade de maiores estudos para descrever a magnitude desse fenômeno no cenário brasileiro e reforçam a importância da presente investigação.…”
Section: Discussionunclassified
“…Os erros de medicação foram significativamente associados ao aumento do número de pacientes atribuídos às enfermeiras (20,22) e foi evidenciado que a maior frequência desses erros nos hospitais ocorrem em unidades de internação (23) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The turbulent hospital environment in which nurses administer medications was explicated by Jennings, Sandelowski, and Mark () in an ethnographic study of MA on two adult acute care units in a large community hospital. Following field observations and interviews, the authors concluded “the nurse's day was defined by medication administration” (p. 1442).…”
Section: Review Of the Literaturementioning
confidence: 99%